The Utilization of Funnel Marketing in Increasing Customer Lifetime Value at LKP Syntax Training Center - Askarno Askarno (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
In the era of digital transformation, training institutions are required not only to attract new participants but also to build long-term relationships. Funnel marketing is an effective strategy, directing potential participants from awareness to becoming loyal customers. This study explores the application of funnel marketing to increase customer lifetime value (CLV) at LKP Syntax Training Centre, a certified training institution in Indonesia. Using a blended approach with a case study design, data was collected through digital marketing and management team interviews, promotional documentation analysis, and CRM data related to conversions, retention, and repurchases. The results show that at each stage of the funnel—awareness through educational content and digital advertising, interest through webinars and email nurturing, decisions through certification promo programs, and retention through loyalty programs and communication automation—can increase CLV, with retention being the most crucial stage, contributing 35% to repeat revenue. Research confirms that a systematic funnel marketing strategy can create a more meaningful participant experience, encourage repurchase, and extend relationships with institutions. Practical implications include strengthening content in the early stages to attract relevant participants as well as leveraging automation and data analytics to maintain loyalty. These findings are expected to be a strategic reference for other training institutions in optimizing digital marketing with a long-term impact.